Self-esteem, optimism and their associated factors among Optometry students at the University of Lahore - Mudassar Ali Roomi; Ansa Farooq; Ahmad Bilal; Shagufta Khaliq; Hafsa Iqbal; Muhammad Imran Ashraf (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Self-esteem and optimism are important for students’ success. Our objectives were (a) to determine self-esteem and life-orientation (optimism) levels among Optometry students in the Department of Optometry & Vision Sciences at the University of Lahore (UoL) (b) to investigate associations between sociodemographic factors, self-esteem, and optimism. METHODOLOGY: This cross-sectional study was conducted during November 2021 to December 2021 at the Department of Optometry and Vision Sciences, UoL. A total of 168 Optometry students were recruited by convenience sampling. Self-esteem was estimated using Rosenberg Self-Esteem Questionnaire. Life Orientation Test-Revised (LOT-R) questionnaire was used to measure optimism. Ethical approval was obtained from the Institutional Review Board of the UoL. Chi-square was used to determine associations between sociodemographic variables, self-esteem, and optimism. RESULTS: Mean self-esteem score was 18.48±3.86 (range:8-30). About 20% of students had low self-esteem. The mean life orientation score was 14.15±2.8 (range:5-24). About 43% of students had low optimism. Significant associations were found between self-esteem, reason of admission in the Optometry program with p-value=0.001, family income p=0.037 , choice of the Optometry program p=0.036, and reason of admission in the Optometry program 0.032. CONCLUSION: Low self-esteem and low optimism have been observed among a significant percentage of Optometry students at the UoL. Reason of admission in the Optometry program and family income were significantly associated factors. Students’ own decision to choose a study program may increase their self-esteem and optimism. Financial assistance for students from the low socioeconomic background may be a positive approach to boost their self-esteem and optimism. Teachers, parents, and counselors should support the students to increase their self-esteem and optimism.